The COVID-19 vaccination campaign in Bhutan: strategy and enablers - Tsheten Tsheten; Phurpa Tenzin; Archie C. A. Clements; Darren J. Gray; Lhawang Ugyel; Kinley Wangdi (BMC, 2022)
Abstract Bhutan has reported a total of 2596 COVID-19 cases and three deaths as of September 15, 2021. With support from India, the United States, Denmark, the People's Republic of China, Croatia and other countries, Bhutan was able to conduct two rounds of nationwide vaccination campaign. While many countries struggle to overcome vaccine refusal or hesitancy due to complacency, a lack of trust, inconvenience and fear, escalated in some countries by anti-vaccine groups, Bhutan managed to inoculate more than 95% of its eligible populations in two rounds of vaccination campaign. Enabling factors of this successful vaccination campaign were strong national leadership, a well-coordinated national preparedness plan, and high acceptability of vaccine due to effective mass communication and social engagement led by religious figures, volunteers and local leaders. In this short report, we described the national strategic plan and enabling factors that led to the success of this historical vaccination campaign.